Pengembangan Usaha Industri Rumah Tangga Opak Singkong Melalui E- Commerce - Alifian Nugraha (Cv. Utility Project Solution, 2022)
E-commerce is a platform that can be used to develop a business by utilizing technology. The role of e-commerce is currently becoming dominant for independent businesses, home industry andmsMEs. Because through e-commerce business actors can market their barang without being limited by place and time, as well as a wide market reach. Business development in e-commerce can make buyers and sellers easily connected quickly to make transactions and what buyers want can be quickly responded to by sellers so that customer satisfaction is achieved and increase seller profits (Rehatalanit, 2021). The home industry business of cassava opak chips is afeed business that in the marketing process does not utilize e-commerce in its marketing so it is difficult to compete with other businesses. Seto the purpose of this devotion is to provide the science and practice of making e-commerce to partners to develop usaonly. This service was carried out with business owners and employees of cassava opoak chips, Mrs. Rupiah in the Sruni Village area, Jenggawah District, Jember Regency. The methods used are observation, documentation, literature study, socialization, training, monitoring and evaluation. The results of community service activities, especially to household industry partners of cassava opak chips, provide changes, especially in the knowledge of business development through e-commerce, skills in making and managing e-commerce and increasing sales through e-commerce.